THE 60h ANNIVERSARY OF ALMETYEVSK STATE OIL INSTITUTE: ON THE WAY TO MODERNIZATION AND RENEWAL - Robert Z. Nurgaliev (Высшее образование в России)
The article highlights the activities of Almetyevsk State Petroleum Institute, its contribution to the development of professional oil education in Russia. The Institute cherishes and upholds the traditions of Tatar Evening Department of the State Academy of Oil and Gas named after I.M. Gubkin allowing it to keep the leading positions in the region. The article views the new tasks and challenges that arise from the structural modernization and renewal of higher technical education with an emphasis on training of managers and elite engineering personnel for innovative segments of the regional oil industry.